Building the foundation for universal healthcare: Academic family medicine's ability to train family medicine practitioners to meet the needs of their community across the globe - Esther M. Johnston; Nath Samaratunga; Ramakrishna Prasad; Bassim Birkland; Klaus B. von Pressentin; Shailendra Prasad (AOSIS, 2022)
Background: The Declaration of Astana marked a revived global interest in investing in primary care as a means to achieve universal healthcare. Family medicine clinicians are uniquely trained to provide high-quality, comprehensive primary care throughout the lifespan. Yet little focus has been placed on understanding the needs of family medicine training programs. Aim: This study aims to assess broad patterns of strengths and resource challenges faced by academic programs that train family medicine clinicians. Methods: An anonymous online survey was sent to family medicine faculty using World Organization of Family Doctors (WONCA) listservs. Results: Twenty-nine representatives of academic family medicine programs from around the globe answered the survey. Respondents cited funding for the program and/or individual trainees as one of either their greatest resources or greatest limitations. Frequently available resources included quality and quantity of faculty and reliable clinical training sites. Frequently noted limitations included recruitment capacity and social capital. Over half of respondents reported their program had at some point faced a disruption or gap in its ability to recruit or train, most often because of loss of government recognition. Reflecting on these patterns, respondents expressed strong interest in partnerships focusing on faculty development and research collaboration. Lessons learnt: This study provides a better understanding of the challenges family medicine training programs face and how to contribute to their sustainability and growth, particularly in terms of areas for investment, opportunities for government policy and action and areas of collaboration.